Indikator sirkularitas di dalam tata kelola limbah pabrik kelapa sawit studi kasus: limbah cair (pome) pabrik kelapa sawit - Yunaningsih, Ani; Satriadi, Yudi; Mauluddin, Amras (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This research was motivated by the problem of liquid waste from palm oil mills. The research aims to find out and understand the current form of palm oil mill waste management, to find out the factors that support palm oil mill waste governance in realizing a circular economy. Determining circularity indicators is one method to see the performance of palm oil liquid waste processing (POME) management and is a benchmark for the level of circularity of palm oil mill governance. The research approach uses the MCI circularity indicator developed by the Ellen MacArthur Foundation in assessing circularity indicators for various POME waste management scenarios in palm oil mills. From various POME processing governance scenarios, namely: 1) Based on field practices in palm oil mills, 2) Based on government regulations regarding POME processing in palm oil mills, 3) Processing POME with biogas technology with an open pond system, 4) Processing POME with biogas technology with a CSTR system, and 5) Processing POME into fertilizer. Based on the assessment results of various scenarios, the MCI circularity values for PKS A, B, and C under existing conditions are as follows: 0.6009 for the current system, 0.5500 for compliance with regulations, 0.5781 for biogas processing with closed ponds, 0.6143 for biogas processing with CSTR, and 0.7065 for fertilizer production. The highest circularity value of 0.7065 is achieved through the scenario of processing POME into fertilizer. This shows that liquid waste management by palm oil mills in Indonesia is still dominated by traditional systems in the form of open ponds.